Individual Differences in Prototypical Moral and Conventional Judgments and Children's Proactive and Reactive Aggression. Issue 4 (13th February 2017) - Jambon, Marc; Smetana, Judith G.
Abstract : This article examined links between 4‐ and 6‐year‐olds' ( n  = 101; M age  = 5.12 years, SD  = 0.67; 53% male) ability to distinguish moral and conventional transgressions along different criteria and teacher ratings of proactive and reactive aggression. Latent difference score modeling revealed that moral transgressions were judged more unacceptable and wrong independent of rules and authority than conventional violations, but significant variability in moral–conventional distinctions was also observed. Proactive aggression was associated with less—and reactive aggression was associated with greater—differentiation in moral and conventional concepts. Proactive aggression was not associated with deficits in moral knowledge when other common assessments of early moral understanding were employed, highlighting the importance of using theoretically informed measures of moral judgments and aggression.